2016
DOI: 10.18632/oncotarget.9840
|View full text |Cite
|
Sign up to set email alerts
|

MYC-dependent recruitment of RUNX1 and GATA2 on the SET oncogene promoter enhances PP2A inactivation in acute myeloid leukemia

Abstract: The SET (I2PP2A) oncoprotein is a potent inhibitor of protein phosphatase 2A (PP2A) that regulates many cell processes and important signaling pathways. Despite the importance of SET overexpression and its prognostic impact in both hematologic and solid tumors, little is known about the mechanisms involved in its transcriptional regulation. In this report, we define the minimal promoter region of the SET gene, and identify a novel multi-protein transcription complex, composed of MYC, SP1, RUNX1 and GATA2, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 74 publications
2
33
0
Order By: Relevance
“…However, reporter assay showed that Sp1 overexpression failed to impact the transcript 2 promoter activity. This is in a sharp contrast to the transcript 1 promoter that was reported to be activated by Sp1 in HEK 293, HeLa, and Acute Myeloid Leukemia (AML) cells HL-60 and HEL [21,22]. Such a discrepancy points to the distinct transcriptional regulation between the two SET transcripts.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, reporter assay showed that Sp1 overexpression failed to impact the transcript 2 promoter activity. This is in a sharp contrast to the transcript 1 promoter that was reported to be activated by Sp1 in HEK 293, HeLa, and Acute Myeloid Leukemia (AML) cells HL-60 and HEL [21,22]. Such a discrepancy points to the distinct transcriptional regulation between the two SET transcripts.…”
Section: Discussionmentioning
confidence: 66%
“…Quantitatively, the expression levels of transcript 2 tend to be more stable than those of transcript 1 [2]. Several studies have concentrated on the transcriptional regulation of transcript 1, and found Sp1 and NF-κB to be the major factors regulating transcript 1 promoter activity [19,21,22]. However, the regulation of SET transcript 2 promoter remains to be a knowledge gap.…”
Section: Introductionmentioning
confidence: 99%
“…Primary antibodies used for immunoblotting and DNA dot blot were anti-phospho-Src (Y419, Cell Signaling Technology), anti-α-tubulin (Sigma), anti-lamin B1 (Abcam), anti-histone H3 (Cell Signaling Technology), anti-p150 (Cell Signaling Technology), anti-p60 (Bethyl Laboratory), anti-GAPDH (Abcam), anti-E-cadherin (Cell Signaling Technology), anti-β-catenin (Cell Signaling Technology), anti-claudin (Cell Signaling Technology), anti-snail1 (Cell Signaling Technology), anti-snail2 (Cell Signaling Technology), anti-vimentin (Cell Signaling Technology), anti-GFP (Roche), and anti-methylcytidine (Abcam) antibodies. Immunoprecipitations were performed as previously described (36). In brief, whole cellular extracts were prepared in co-immunoprecipitation buffer (PBS containing 0.5% Triton X-100, 1 m m EDTA, 100 m m sodium orthovanadate, 0.25 m m PMSF, complete protease inhibitor (Roche)).…”
Section: Methodsmentioning
confidence: 99%
“…However, reporter assay showed that Sp1 overexpression failed to impact the transcript 2 promoter activity. This is a sharp contrast to the transcript 1 promoter that was reported to be activated by Sp1 in HEK 293, HeLa and Acute Myeloid Leukemia (AML) cells HL-60 and HEL [21,22]. Such a discrepancy points to the distinct transcriptional regulation between the two SET transcripts.…”
Section: Discussionmentioning
confidence: 64%
“…Quantitatively, the expression levels of transcript 2 tend to be more stable than those of transcript 1 [2]. Several studies have concentrated on the transcriptional regulation of transcript 1, and found Sp1 and NFkB to be the transcription factors regulating transcript 1 promoter activity [19,21,22]. However, the regulation of SET transcript 2 promoter remains to be a knowledge gap.…”
Section: Introductionmentioning
confidence: 99%